PENGARUH PERSEPSI PEMBAYARAN CASH ON DELIVERY (COD) DAN GRATIS ONGKIR TERHADAP MINAT BELI PADA MASYARAKAT PENGGUNA APLIKASI SHOPEE ( STUDI KASUS MASYARAKAT DESA SELOGUDIG WETAN) - Lailiyah, Warda; Wisudaningsih, Endah Tri; Aqidah, Waqi’atul (Program Studi Manajemen Fakultas Ekonomi UST, 2024)
In making a purchase, customers weigh the advantages and disadvantages of the available options and choose a course of action based on their evaluation “ Free shipping and Cash On Delivery (COD) are two of the many elements that influence customer shopping. Researchers aim to find out whether there is an influence of free shipping and Cash On Delivery (COD) on people's buying interest. This research uses quantitative methods with a descriptive approach. The population in this study was 593 residents of Selogudig Wetan village aged 20-29 years. With a sample of 240 respondents selected using the Slovin formula sampling method. Data collection was carried out by distributing questionnaires. Using multiple linear regression analysis techniques, used for data processing and analysis with the SPSS application. The results of data analysis show that the questionnaire test instrument is declared valid and reliable and there are no violations in the classical assumption test. Based on the findings of this research, it can be concluded that Cash On Delivery (COD) payments and free shipping have a significant effect on purchasing interest, as shown by the F test, calculated F is greater than F table. In addition, the partial T test produces a significance value of less than 0.05, which indicates that the two independent variable factors partially influence buying interest.